The functional anatomy and physiology of the gustatory system - Spector, Alan (Henry Stewart Talks, 2026)
The relationship between physicochemical properties of a compound and taste perception, Taste buds, Transduction pathways for taste stimuli, Anatomy of the ascending rodent gustatory system, Domains of taste function, Testing taste function in rodent models, Functional role of gustatory pathways